Feeding ecology of the two sympatric fish species Notothenia rossii and N. coriiceps from western Antarctic Peninsula: a fatty acids and stable isotopes approach - Moreira, María Eugenia; Martínez Novillo, Manuel; Mintenbeck, Katja; Barrera Oro, Esteban; De Troch, Marl
Biomarker analysis, especially fatty acids (FA) and stable isotopes (SI), has become a useful tool to elucidate the flow of energy and trophic interactions in an ecosystem and to analyse the diet of species that are hard to observe while feeding. Herein we compare FA profiles and SI composition (nitrogen, δ 15N and carbon, δ 13C) of muscle tissue from two sympatric Antarctic fish species - Notothenia rossii and N. coriiceps – that are key components in the inshore ecosystem of the South Shetland Islands. For both nototheniids, potential food sources from the benthic community (algae, amphipods, polychaetes and gastropods) were screened in order to re-evaluate their trophic position (TP) and the energy flow, taking as representative of the area the local food web of Potter Cove, in King George Island/Isla 25 de Mayo. Significant differences in FA and SI composition between the two fish species (δ15N / δ13C N. rossii: 9.94±0.80‰ / -23.64±1.03‰, N. coriiceps: 11.44±0.42‰ / -21.46±0.46‰) were found. Notothenia rossii showed a higher total FA concentration, with high levels of polyunsaturated FA (PUFA) such as EPA, DHA and ARA. Conversely, the potential food sources tested showed low concentrations of these FAs. This could indicate that both nototheniids are feeding mainly on another food source that was not included in the present study, or that FA bioconversion takes place in these species. While the FA results might suggest a possible trophic niche segregation between N. rossii and N. coriiceps, both species occupy a similar TP (N. rossii = 3.1, N. coriiceps = 3.5). Furthermore, we found a higher total concentration of monounsaturated FA (MUFA) in N. rossii (4348.4 μl/µg) than in N. coriiceps (85.6 μl/µg), which is about 50-fold greater, and is related with a higher buoyancy capacity in N. rossii. In the present study the use of trophic biomarkers did not elucidate which was the main prey item as lipid source for N. rossii and N. coriiceps, suggesting that other food sources need to be analysed and the species ...